Rancangan Media Pembelajaran Biologi Kelas XI Berbasis Augmented Reality di MAN 2 Agam - Annisa, Sherly; Efriyanti, Liza; Zakir, Supratman; Supriadi, Supriadi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research was conducted from the problems found after observations at MAN 2 Agam found the problem that students and teachers only rely on manual learning and still use printed books without using learning media. So that teachers only use simple tools in teaching and learning activities that make students bored and less interested in repeating the material that has been explained about the